Cell blocks allow reliable evaluation of expression of basal (CK5/6) and luminal (CK8/18) cytokeratins and smooth muscle actin (SMA) in breast carcinoma - Delgallo, W. D. [UNESP]; Rodrigues, José Ricardo Paciência [UNESP]; Bueno, S. P. [UNESP]; Viero, Rosa Marlene [UNESP]; Soares, C. T. (Wiley-Blackwell, 2010)
Objective:Gene expression studies have revealed several molecular subtypes of breast carcinoma with distinct clinical and biological behaviours. DNA microarray studies correlated with immunohistochemical profiling of breast carcinomas using cytokeratin (CK) markers, Her2/neu, oestrogen receptor (ER), and basal myoepithelial cell markers have identified five breast tumour subtypes: (i) luminal A (ER+; Her2/neu-), (ii) luminal B (ER+; Her2/neu+), (iii) Her2 overexpression (ER-; Her2/neu+), (iv) basal-like (ER-; Her2/neu-, CK5/6 and 14+), and (v) negative for all markers. Luminal carcinomas express cytokeratins in a luminal pattern (CK8/18), and the basal-like type expresses CK5/6 and CK14 or basal epithelial cell markers. CK5/6, CK8/18, and smooth muscle actin (SMA) expression were assessed in cell blocks and compared with expression in surgical specimens.Methods:Sixty-two cases of breast carcinoma diagnosed by fine needle aspiration cytology with cell blocks and available surgical specimens were included. Cell blocks containing at least 10 high-power fields each with at least 10 tumour cells and surgical specimens were immunostained for CK5/6, CK8/18 and SMA.Results:Percentage sensitivity, specificity, positive predictive value, negative predictive value and accuracy were, respectively, 77, 100, 100, 92 and 94 for CK5/6; 98, 66, 96, 80 and 95 for CK8/18; and 92, 96, 85, 98 and 95 for SMA.Conclusion:The identification of CK5/6, CK8/18 and SMA by immunohistochemistry in cell blocks can be a reliable method that yields results close to those obtained in surgical specimens, and can contribute to the classification of breast carcinomas with luminal and basal expression patterns, providing helpful information in the choice of treatment and in the evaluation of prognostic and predictive factors.
Keywords: breast cancer; fine needle aspiration cytology; basal and luminal cytokeratins; cell blocks; immunohistochemistry